El problema de la consciencia y su brecha explicativa en la psicología (2012)
This article reflects on the explanatory gap in the problem of consciousness within the mind-body problem. Despite the theoretical developments in multiple disciplines, consciousness still eludes the gaze of science. Particularly, it can be argued that psychology has left the issue aside, and has been engaged in the investigation of phenomena subordinate to consciousness. Therefore, it is expected that in coming years the whole of science in general, thinks the problem in a new way and breaks through to the object that has captivated from the old philosopher to the current scientific.